The last diving horse in America : rescuing Gamal and other animals -- lessons in living and loving - Branigan, Cynthia A. (Pantheon Books, 2021)
"It was the signature attraction of Atlantic City's Steel Pier from the 1930s to the 1970s, the golden age of "America's Favorite Playground"--Doc Carver's High Diving Horses. Four times a day, seven days a week, a trained horse wearing only a harness ran up a ramp; a diving girl jumped on its back, and both sailed forty feet through the air, plunging into a ten foot deep tank of water. Decades later, after cries of animal abuse, and changing times, the act was finally shuttered and the very Last Atlantic City Steel Pier Diving Horse was on the auction block, with the author on a rescue mission. And $2,600 later, Gamal, gleaming coated, commanding, was hers: she who knew almost nothing about horses. Cynthia Branigan tells the story of how horse and new owner, come to know and educate and trust one another; teaching each other important lessons of living and loving. Branigan writes of the history of diving horses and how rescuing and caring for Gamal led her to save other animals, at first as company for Gamal--burros, and others, and then finally, saving a 10 year-old retired Greyhound, nearly broken in spirit, who, with Gamal, came back to his happy self, and opened up for the author a new and purposeful world"--